2017
DOI: 10.3390/cli5040086
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis of the Relationship between Brown Haze and Surface Air Pollution Levels on Respiratory Hospital Admissions in Auckland, New Zealand

Abstract: Eleven years of hospital admissions data for Auckland, New Zealand for respiratory conditions are analyzed using a Poisson regression modelling approach, incorporating a spline function to represent time, based on a detailed record of haze events and surface air pollution levels over an eleven-year period, taking into account the daily average temperature and humidity, the day of the week, holidays and trends over time. NO 2 was the only pollutant to show a statistically significant increase (p = 0.009) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…In our study, we used the 90th and 95th percentiles of PM 10 concentrations (i.e., 87.1 μg/m 3 and 109.6 μg/m 3 , respectively) to identify days of biomass burning exposure, which is slightly lower than the 99 percentile employed by Morgan et al [35]. A range of other approaches also have been employed to identify days with exposure to burning, or haze, including a doubling of total suspended particulates (mean = 56.9 μg/m 3 [49]), the extent of discoloration in the sky [36], a threshold of 80 μg/m 3 to indicate 'unhealthy' levels [50], and exposure in the month of March [46]. Other studies of exposure to fires have employed software to track polluted air mass trajectories based on meteorological data (e.g., [51]).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, we used the 90th and 95th percentiles of PM 10 concentrations (i.e., 87.1 μg/m 3 and 109.6 μg/m 3 , respectively) to identify days of biomass burning exposure, which is slightly lower than the 99 percentile employed by Morgan et al [35]. A range of other approaches also have been employed to identify days with exposure to burning, or haze, including a doubling of total suspended particulates (mean = 56.9 μg/m 3 [49]), the extent of discoloration in the sky [36], a threshold of 80 μg/m 3 to indicate 'unhealthy' levels [50], and exposure in the month of March [46]. Other studies of exposure to fires have employed software to track polluted air mass trajectories based on meteorological data (e.g., [51]).…”
Section: Discussionmentioning
confidence: 97%
“…For cardiovascular outcomes, short-term exposure to PM has been associated with such changes as reduced heart rate variability, increased diastolic blood pressure, and enhanced arterial vasoconstriction and blood coagulation, all of which may contribute to acute events [32]. Larger risks on the same day of PM 10 exposure compared to lagged estimates have also been identified in urban contexts, including all hospital admissions in 218 Chinese cities [33], COPD admissions in Beijing [22], and also specifically with biomass burning: bushfire and respiratory admissions in Australia [34,35], and haze and respiratory admissions in New Zealand (ages 15-64 years only [36]). Our results with CBVD visits, but not IHD, conflict with findings from Morgan et al [35], where a relationship with cardiovascular admissions was not identified using any lag.…”
Section: Discussionmentioning
confidence: 99%
“…The population in the urban area is approximately over 100,000 people, whereas the population can vary from 10,000 to 100,000 people for suburban area, and population in rural area is usually under 10,000 people. Previous studies conducted by several researchers stressed that building's age [27][28][29] and location [34][35][36][37][38][39][40][41][42][43][44] are important to be considered when assessing building characteristics. The summary of the matrix score criteria (Criteria 4) classifying the museum's characteristics into different risk possibilities namely low potential risk, medium potential risk, high potential risk, or extreme potential risk, as shown in Table 14.…”
Section: Building Characteristicmentioning
confidence: 99%
“…reported, in Kuopio (Finland) [13] and Auckland (New Zealand) where Dirks et al [14] demonstrate the relation between daily mortality and local traffic-related air pollutants.…”
mentioning
confidence: 97%